Has bank digitization facilitated green transformation of enterprises? - Jia, Kaiwei; Zhang, Yu; Zheng, Yanting (Frontiers in Environmental Science, 2024)
Based on measuring the green transformation of heavily polluting enterprises based on the subdimensions of green strategy and green action, we empirically analyze whether and how bank digitization affects the green transformation of enterprises by using the data of China's A-share heavily polluting enterprises from 2010 to 2021. The findings show that (1) bank digitization has a significant positive effect on firms' green transformation; (2) bank digitization promotes firms' green transformation by alleviating firms' financing constraints and improving firms' ESG performance; (3) governmental environmental regulations and media attention positively moderates the relationship between bank digitization and firms' green transformation; and (4) bank digitization is more likely to promote the green transformation of firms that are highly digitized, non-state-owned firms, and enterprises in the eastern region; (5) the sub-dimension test shows that bank digitization has significant differences on different dimensions of green transformation. The above analysis shows that bank digitization should be deeply integrated with the green transformation of enterprises, and the former should be deeply embedded in supervising, forcing and empowering enterprises to upgrade environmental protection technology and sewage treatment, and the regulator should formulate a more detailed environmental protection disclosure program to realize the consistency "words" and "deeds" of the green transformation of enterprises.